Reading and freedom in the writings of the young Nietzsche (Revista de História Regional, 2008)
The aim of this article is the theme of freedom andthe self in the autobiographic writings and correspondence ofthe young Nietzsche in the beginning of the 1870s. His readingand writing showed a path to freedom, possibility the self andfighting the non-free elements that the young Nietzsche couldsee in his time and even in himself. The young Nietzsche feltthe need to free himself to develop an artistic style of writing,corresponding to the sound of good music, in order to do so, helonged for a community of readers / writers who could sharecommon goals and pleasures.